2002
DOI: 10.3168/jds.s0022-0302(02)74255-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abomasal Vegetable Oil Infusion on Splanchnic Nutrient Metabolism in Lactating Dairy Cows

Abstract: Changes in the metabolism of nutrients by the portal-drained viscera (PDV) and liver may contribute to the reduction in dry matter intake (DMI) and other production responses generally observed in lactating dairy cows fed supplemental long-chain fatty acids (LCFA). In the present study, effects of a 7-d abomasal infusion of vegetable oil on arterial concentration and splanchnic (PDV and liver) metabolism of nutrients were measured in six cows at 55 (early lactation [ELAC]) and 111 (midlactation [MLAC]) d postp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 28 publications
12
45
1
3
Order By: Relevance
“…The liver uptake of propionate relative to the net release from the PDV, comprising the fore stomachs and intestines, has been observed to be high around 90% to 95% (Reynolds et al, 2003; Figure 4b) as also observed in established lactations and other ruminants (Reynolds et al, 1988a;Bergman, 1990;Benson et al, 2002). Further, the liver propionate uptake relative to net PDV release was relatively constant during the periparturient period (P lin.…”
Section: Liver Uptake Of Glucogenic Vfamentioning
confidence: 73%
See 1 more Smart Citation
“…The liver uptake of propionate relative to the net release from the PDV, comprising the fore stomachs and intestines, has been observed to be high around 90% to 95% (Reynolds et al, 2003; Figure 4b) as also observed in established lactations and other ruminants (Reynolds et al, 1988a;Bergman, 1990;Benson et al, 2002). Further, the liver propionate uptake relative to net PDV release was relatively constant during the periparturient period (P lin.…”
Section: Liver Uptake Of Glucogenic Vfamentioning
confidence: 73%
“…The relatively slow post partum increase of expression of mRNA for propionyl-CoA carboxylase and phosphoenolpyruvate carboxykinase (PEPCK) in liver tissue (Greenfield et al, 2000;Aschenbach et al, 2010) may be limiting the liver uptake of propionate. It could also be speculated that the post partum increase in liver metabolism of non-esterified fatty acids has negative effects on liver uptake of propionate; however, Benson et al (2002) did not observe changes in liver uptake of propionate in response to increased liver uptake of nonesterified fatty acids from abomasally infused vegetable oils. Yet, this does not preclude increased non-glucogenic liver use of propionate.…”
Section: Liver Uptake Of Glucogenic Vfamentioning
confidence: 84%
“…The butyrate fermentation following intake of grass with high sugar content might be part of the explanation for the typical decreasing milk production and milk fat production experienced when cows start to graze in the spring. In an experiment with intraruminal infusion of Figure 4 Portal-drained visceral (PDV) extraction of arterial urea-nitrogen in lactating dairy cows plotted against the arterial concentration of urea-N. Means from the following studies were used to establish the regression line (R 2 5 0.50) closed square (Reynolds et al, 2003); closed triangle up (Benson et al, 2002); closed triangle down (Blouin et al, 2002); closed diamond (Delgado-Elorduy et al, 2002a); closed hexagon (Delgado-Elorduy et al, 2002b); open square (Casse et al, 1994); open triangle down (Bach et al, 2000); open triangle up (Berthiaume et al, 2006); closed circle (Reynolds et al, 1988b); and open circle (Raggio et al, 2004). The mean PDV extraction of urea-N observed in the present study is indicated as an open diamond.…”
Section: Hourmentioning
confidence: 99%
“…As concentrações de glicose circulante possibilitam aos receptores neurais no eixo hipotalâmico (centro da fome e da saciedade) o termino das refeições, conhecido como controle químico (BENSON et al, 2002 O consumo de proteína bruta (PB) apresentou efeito linear decrescente (P<0,05). Para cada um % de GB incluída na dieta houve uma redução de 0,010 kg de PB dia -¹, sendo essa resposta devido à redução do concentrado farelado na composição das dietas com maiores teores de GB, que em sua composição era isenta de PB.…”
Section: Consumounclassified